2021
DOI: 10.3390/membranes11080571
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Indole-3-Propionic Acid Reduce Oxidative Damage to Membrane Lipids Induced by High Iron Concentrations in Porcine Skin

Abstract: Iron excess in tissues results in increased oxidative damage. Among different tissues, the skin can particularly be severely damaged by oxidative stress, as it is exposed not only to endogenous but also directly to exogenous pro-oxidants. The skin is especially vulnerable to harmful oxidative stress. Melatonin and indole-3-propionic acid (IPA), two indole substances, are efficient antioxidants. This study aims to evaluate the potential protective effects of melatonin and IPA against oxidative damage to membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…found that indoleacrylic acid, but not indolepropionic acid, had an anti-oxidative and anti-inflammatory function in LPS-activated human peripheral blood mono-nuclear cells, which reduced IL-6 and IL-1β secretion, and activated the NRF2-ARE pathway ( 31 ). Indole-3-propionic acid protected cells from reactive oxygen species (ROS), oxidative damage, and lipid peroxidation ( 32 34 ). In the current study, dietary ICA supplementation in pigs did not change the antioxidant enzyme activities in serum, including SOD, GSH-Px, CAT, T-AOC, and MDA, suggesting ICA have no anti-oxidative effect in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…found that indoleacrylic acid, but not indolepropionic acid, had an anti-oxidative and anti-inflammatory function in LPS-activated human peripheral blood mono-nuclear cells, which reduced IL-6 and IL-1β secretion, and activated the NRF2-ARE pathway ( 31 ). Indole-3-propionic acid protected cells from reactive oxygen species (ROS), oxidative damage, and lipid peroxidation ( 32 34 ). In the current study, dietary ICA supplementation in pigs did not change the antioxidant enzyme activities in serum, including SOD, GSH-Px, CAT, T-AOC, and MDA, suggesting ICA have no anti-oxidative effect in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…IS, the liver metabolite of microbiota-derived indole, promotes the production of reactive oxygen species (ROS) [124] and induces expression of proinflammatory cytokines, including IL-1β [125], TNF-α [125] and MCP-1 [125][126][127]. Interestingly, IPA protects cells from ROS [25,128,129], oxidative damage and lipid peroxidation caused by potassium bromate [130][131][132], potassium iodate [24], iron (II) sulphate [133,134], iron (III) chloride [135], chromium (III) chloride [136], and 2,2 -Azino-bis(3-ethylbenzothiazoline-6sulfonic acid (ABTS) [137]. Additionally, IPA decreases the expression of proinflammatory cytokines, including TNF-α [22,27,121], IL-1β [23,27], IL-6 [27], IL-12 [22], IL-13 [22] and MCP-1 [22,82].…”
Section: Ipa Protects Against Oxidative Stress and Attenuates Inflamm...mentioning
confidence: 99%
“…Melatonin has antioxidative action, and also increases clearance of amyloid β-protein in the mice model of Alzheimer's disease amyloidosis [157]. IPA shares protective biological effects against oxidative stress with melatonin [24,133] and decreases aggregation of amyloid β-protein in in vitro experiments [158]. The addition of IPA to media of the primary neurons and neuroblastoma cells exposed to amyloid β-protein significantly reduced toxicity and prevented cell death [159].…”
Section: Ipa In Alzheimer's Diseasementioning
confidence: 99%
“…Until now, Fenton reaction substrates were used very commonly to experimentally induce oxidative damage to macromolecules in different tissues (e.g., ovary, thyroid, and skin) with very high Fe 2+ concentrations (Rynkowska et al, 2020(Rynkowska et al, , 2021, equal to these used in the present study.…”
Section: Introductionmentioning
confidence: 99%